Is there a relationship between macroeconomic variables and stock market indices in Bosnia and Herzegovina? - Abdić, Adem (Naše gospodarstvo, 2024)
The economic growth and development of a country are reflected in many aspects, one of them being the stock market indices. The purpose of the article is to examine and determine the relationship between selected macroeconomic variables and stock market indices in Bosnia and Herzegovina (BiH). Using quarterly data over the 2010q1-2019q4 period, a cointegration analysis was applied to model this relationship. The Vector Error Correction Model (VECM) was used to explore the short-run relationship as well as the long-run relationship. The article examined the predictive ability among variables of interest by applying the Granger causality test. The results indicate a stable long-run relationship between the analysed macroeconomic variables and stock market indices in BiH, while no short-run relationship was found. The results contribute to the scientific discussions about the relationship between selected macroeconomic variables and representative stock market indices in BiH which considers their direction and strength.
Keywords: BiH; borze; Bosna in Hercegovina; finance; Granger causality test; macroeconomic variables; stock market indices; trg vrednostnih papirjev; VECM model